Literary Ecologies of the Indian Ocean. Issue 1 (2nd January 2019) - Hofmeyr, Isabel
Abstract: This article explores themes of literary ecologies and oceanic studies as a framework for a selection of articles. The article begins by outlining older approaches to oceanic studies which treat the ocean as surface and backdrop to human activity at sea. Rising sea levels and climate change, however, demand new approaches that can engage the materiality of the ocean, its surface and depth. This shift from surface to depth has prompted a set of new immersive methods that seek to go below the waterline. Drawing on these methods, the article proposes the rubric of hydrocolonialism which is defined and discussed. The article provides a discussion of the articles that foregrounds the oceanic, ecological and hydrocolonial themes in each.